Impact of Porous Media and Magnetic Field on Peristaltic Transport of a Second-Grade Dusty Fluid Through a Symmetric Channel - Addullah, Fatima K.; Abdulhadi, Ahmed M. (Iraqi Journal of Science, 2025)
In this research, we studied the effect of porous media, magnetic field, and heat transfer on the peristaltic flow of a second-order dusty fluid in a symmetrical cylindrical channel. The coupled nonlinear differential equations, which represent the motion of dust and fluid molecules, are formulated. These equations are solved by using the perturbation method with the help of the mathematics package; we obtained an approximate analytic solution. The impact of different kinds of parameters, like the Prandtl number, Renold number, wave number, second-grade parameter, Hartman number, wave length, permeability of the medium, and Darcy number, is discussed on the fluid velocity, fluid temperature, flow pattern, dust particle flow pattern, and pressure. The results show that increasing the permeability of the porous medium has a negligible effect on the size and number of boluses, with the bolus size decreasing by a small percentage as the Darcy number increases. We observed that the number of boluses decreases and their size increases as the Hartman number increases. Finally, we discussed the results graphically using MATHMETICA software.